Demand Theory of Sharia Micro Economic Perspective - Ririn Makrifah; Miftahur Rahman (FEBI UIN Sunan Kalijaga, 2022)
The purpose of writing this article is to find out about the theory of demand in sharia microeconomics and what is related to the discussion of the theory of microeconomic demand. Economics is a human act as a consumer to fulfill needs and desires or make various requests for various goods and services in everyday life. Islamic economics itself is never separated from moral and religious values because every activity is always associated with the Shari'a. Islamic economics is the knowledge and application of sharia law to prevent injustice in the use and disposal of material resources with the aim of providing human satisfaction and carrying out these activities as an obligation to Allah and society. The Qur'an calls the economy the term istishad (saving, economy) which literally means